Developing Creative Writing Skills through a Short Story-Based Program - Aly A. Qoura, Mervat El Hadidy (Journal of Research in Curriculum, Instruction and Educational Technology, 2023)
The present study aimed to investigate the impact of a program based on short stories to develop EFL secondary school students' creative writing skills (fluency, flexibility, originality and elaboration). To achieve the purpose of the study, two instruments were constructed; a questionnaire of creative writing skills to determine the most important creative writing skills for first year secondary school students and a pre-post creative writing test. The participants of the study consisted of 60 girls divided into two groups; experimental group and control group from first year secondary school students of Sinbellawein secondary school for girls. The results of the study indicated that the use of short story enhanced the creative writing skills of first year secondary school students. It was recommended that EFL course designers include creative writing skills and train teachers on using creative writing activities.